Suppressor of Cytokine Signaling 3 in Macrophages Prevents Exacerbated Interleukin-6-Dependent Arginase-1 Activity and Early Permissiveness to Experimental Tuberculosis - Schmok, Erik; Dar, Mahin Abad; Behrends, Jochen; Erdmann, Hanna; Rueckerl, Dominik; Endermann, Tanja; Heitmann, Lisa; Hessmann, Manuela; Yoshimura, Akihiko; Rose-John, Stefan; Scheller, Juergen; Schaible, Ulrich Emil; et al. (Frontiers in Immunology, 2017)
Suppressor of cytokine signaling 3 (SOCS3) is a feedback inhibitor of interleukin (IL)-6 signaling in macrophages. In the absence of this molecule, macrophages become extremely prone to an IL-6-dependent expression of arginase-1 (Arg1) and nitric oxide synthase (NOS)2, the prototype markers for alternative or classical macrophage activation, respectively. Because both enzymes are antipodean macrophage effector molecules inMycobacterium tuberculosis(Mtb) infection, we assessed the relevance of SOCS3 for macrophage activation during experimental tuberculosis using macrophage-specific SOCS3-deficient (LysMcreSOCS3loxP/loxP) mice. Aerosol infection of LysMcreSOCS3loxP/loxPmice resulted in remarkably higher bacterial loads in infected lungs and exacerbated pulmonary inflammation. This increased susceptibility toMtbinfection was accompanied by enhanced levels of both classical and alternative macrophage activation. However, high Arg1 expression preceded the increased induction of NOS2 and at early time points of infection mycobacteria were mostly found in cells positive for Arg1. This sequential activation of Arg1 and NOS2 expression in LysMcreSOCS3loxP/loxPmice appears to favor the initial replication ofMtbparticularly in Arg1-positive cells. Neutralization of IL-6 inMtb-infected LysMcreSOCS3loxP/loxPmice reduced arginase activity and restored control of mycobacterial replication in LysMcreSOCS3loxP/loxPmice. Our data reveal an unexpected role of SOCS3 during experimental TB: macrophage SOCS3 restrains early expression of Arg1 and helps limitMtbreplication in resident lung macrophages, thereby limiting the growth of mycobacteria. Together, SOCS3 keeps IL-6-dependent divergent macrophage responses such asNos2andArg1expression under control and safeguard protective macrophage effector mechanisms.
EVALuna2:33300